(untitled) (Marketing Journal, 2026)
This article analyzed the role of public -private partnership (PPP) mechanisms in the modernization and sustainable development of Uzbekistan’s energy sector. The study systematically examined key policy reforms, implemented PPP projects, and their economic and environmental impacts. Based on the analysis of international financial institution reports and practical project experience, it was found that PPP mechanisms made a significant contribution to attracting investment, expanding renewable energy capacit y, and strengthening national energy security. The results demonstrated steady growth in solar and hydropower capacities and the formation of a long-term investment pipeline through 2030. The study concluded that the effectiveness of PPPs could be further enhanced through improved risk management practices and stronger institutional coordination.